Reduction of airborne allergenic urinary proteins from laboratory rats. - Gordon, S (1992)
Allergy and asthma caused by proteins of laboratory animals, particularly rats and mice, are the most important occupational health hazards for the scientists and technicians who work with such animals. The influence of different cage litters, cage design, and stock density on measured rat urinary aeroallergen (RUA) concentrations has been examined in a room housing male rats, to determine practical means to reduce allergen concentration in animal laboratories. Eight hour static air samples were taken at 2 1/min and the RUA concentrations measured by radioallergosorbent test (RAST) inhibition. High RUA concentrations occurred when the animals were housed on wood based, contact litter (geometric mean (GM) sawdust 7.79 micrograms/m3; woodchip 6.16 micrograms/m3). The use of noncontact absorbent pads was associated with a significant decrease in RUA concentrations (GM 2.47 micrograms/m3; p less than 0.0001). Rat urinary aeroallergen concentrations fell more than fourfold when the animals were housed on woodbased, contact litter in filter top cages rather than conventional open top cages (GM filter top 0.33 micrograms/m3; open top 1.43 micrograms/m3; p less than 0.0001). The number of rats (stock density) strongly influenced the RUA concentration and a linear relation was found between the log(e) allergen concentration and stock density under these study conditions. The measurement of airborne particle size on cleaning out days showed that all litter types generated similar sized particles: more than 80% of the RUA was carried on particles larger than 8 microns in diameter for all litter types. The findings suggest that the exposure of animal husbandry personnel to RUA may be substantially reduced by the avoidance of contact litter, the use of filter top cages (where suitable), and by keeping stock density to a minimum.